2013
DOI: 10.1007/s11481-013-9477-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Abnormalities During Finger-Tapping in HIV-Infected Older Adults: A Magnetoencephalography Study

Abstract: Despite the availability of combination antiretroviral therapy, at least mild cognitive dysfunction is commonly observed in HIV-infected patients, with an estimated prevalence of 35-70%. Neuropsychological studies of these HIV-associated neurocognitive disorders (HAND) have documented aberrations across a broad range of functional domains, although the basic pathophysiology remains unresolved. Some of the most common findings have been deficits in fine motor control and reduced psychomotor speed, but to date n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 58 publications
8
41
2
Order By: Relevance
“…These results are consistent with many prior studies of beta activity in healthy adults and children (Gaetz et al, 2010; Hall et al, 2011; Heinrichs-Graham et al, in press; Jurkiewicz et al, 2006; Tzagarakis et al, 2010; Wilson et al, 2010, 2011, 2013), which have characterized this response as a marker of movement planning (Doyle et al, 2005; Kaiser et al, 2001). Interestingly, we found that the amplitude of the beta ERD significantly increased from morning to afternoon in recognized regions of the motor network, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with many prior studies of beta activity in healthy adults and children (Gaetz et al, 2010; Hall et al, 2011; Heinrichs-Graham et al, in press; Jurkiewicz et al, 2006; Tzagarakis et al, 2010; Wilson et al, 2010, 2011, 2013), which have characterized this response as a marker of movement planning (Doyle et al, 2005; Kaiser et al, 2001). Interestingly, we found that the amplitude of the beta ERD significantly increased from morning to afternoon in recognized regions of the motor network, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…During the movement task, participants were instructed to fixate on a centrally-presented cross hair and to perform a single flexion-extension of the second metacarpus phalangeal (i.e., index finger) of the right hand each time a dot reached the 12 o’clock position. This dot completed one full rotation around a clock-like circle without tick marks or numbers every 6 s, and was meant to serve as a pacing device (Heinrichs-Graham et al, in press; Wilson et al, 2013). The precise timing of movement onset was determined by a fiber optic switch, whereby a signal was emitted from one side of a groove that functioned as the finger rest area.…”
Section: Methodsmentioning
confidence: 99%
“…For example, an MEG study of motor control demonstrated that HIV-infected patients had reduced beta responses (14-28 Hz) prior to movement onset in the supplementary motor area and bilateral primary motor cortices (stronger on the side contralateral to movement) relative to demographically-matched controls. 82 HIV-infected patients also had increased activity in bilateral prefrontal cortices, which likely reflected compensatory processes serving movement planning, as significant correlations were observed between the amplitude of such activity and performance on the Trail Making Test (A+B). 82 An MEG study of visual attention also found abnormal activity in the right prefrontal cortices, as well as the frontal eye-fields of HIV-infected older adults compared with matched uninfected controls.…”
Section: Hiv-associated Neurocognitive Disorders (Hand)mentioning
confidence: 97%
“…82 HIV-infected patients also had increased activity in bilateral prefrontal cortices, which likely reflected compensatory processes serving movement planning, as significant correlations were observed between the amplitude of such activity and performance on the Trail Making Test (A+B). 82 An MEG study of visual attention also found abnormal activity in the right prefrontal cortices, as well as the frontal eye-fields of HIV-infected older adults compared with matched uninfected controls. 83 Consistent with the motor control study, the magnitude of neural responses in these areas correlated with neuropsychological performance in the HIV-infected patients.…”
Section: Hiv-associated Neurocognitive Disorders (Hand)mentioning
confidence: 97%
“…HIV-infected individuals exhibit deficits in motor functioning, particularly on tasks requiring fine motor movement (Wilson et al 2013), gait (Robertson et al 2006), and postural stability (Bernard et al 2013; Sullivan et al 2011). Impaired motor functioning in HIV-infected individuals was a prominent symptom before the introduction of HAART and comprised a unique diagnostic category before the revision of neurocognitive disorders criteria in 2007 (Antinori et al 2007).…”
Section: Motor Deficits In Hiv Infection and Pdmentioning
confidence: 99%